The ‘Yoke of the Torah’ as a source of joy in Judaism and Jesus’s use of the yoke metaphor in Matthew 11:29–30 - Mulder, Michael (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
In Matthew 11:29–30, Jesus uses the image of a yoke in his interaction with the Pharisees. It is most common to interpret these verses as depicting the Jewish leaders – placing the ‘yoke of the Torah’ upon the people as an oppressive burden, in contrast to Jesus’s teaching, offering a different kind of yoke – one that is light and provides rest for the soul. In this article, it is argued that this contrast is insufficient for an appropriate understanding of Jesus’s use of the yoke metaphor. Firstly, to portray the ‘yoke of the Torah’ as an unbearable burden would be in tension with Jewish tradition, in which this ’yoke’ is regarded as a source of joy. The first part of this article therefore explored the concept of the ‘joy of the Torah’ within Jewish tradition, the very context in which the New Testament was written and within which it should be interpreted. It turned out that this joy is a prominent aspect in Jewish religious life, connected to the image of taking up the ’yoke of the Kingdom’. It is within this view of the term yoke that Jesus speaks to the Jewish leaders. The second part of the article proposed an alternative reading of Jesus’s reference to his own teaching as a ‘yoke’. If Jesus’s message opposed concrete obedience to the Torah, this would not only contradict the understanding of the yoke of the Torah as a source of joy among his audience, but also contradict his own affirmation of the Torah, as, for example, in the Sermon on the Mount. An intertextual analysis of the words used in Matthew 11:28–30 elucidated that Jesus’s use of the yoke metaphor echoes a positive use of this image, specifically by Jeremiah and Ecclesiasticus. Thus, there is much more continuity with the Old Testament and Jewish usage of the yoke metaphor than is suggested in the traditional exegesis of this passage. Contribution: Finally, it is concluded that this not only sheds new light on the use of the yoke metaphor by Jesus in this passage, but it could also stimulate a fruitful dialogue with the Jewish tradition on how to live with the Torah as a source of joy. Moreover, this interpretation aligns with the whole framework of Matthew’s Gospel, never abolishing the Law, as underscored in the dissertation of Francois Viljoen, to whom this contribution is offered as a token of friendship.